Why stay with the police? How meaningfulness in life moderates the mediated effects of role stressors’ appraisals on anxiety and intention to leave the State Brazilian Police - Torres, Cláudio V. (International journal of police science & management, 2022)
Brazilian police officers’ increasing levels of work anxiety and intention to leave the job are consistent with other police forces around the world. Among the important variables that appear to be antecedents of these unwanted organizational outcomes are increasing role stressors associated with police work. We conjecture that how police officers appraise stressors would affect whether adverse outcomes prevail. Specifically, stressors appraised as challenges result in weaker adverse outcomes compared with stressors appraised as hindrances. We also anticipate that a boundary condition that might further attenuate adverse outcomes is having meaningfulness in life (MIL). Likewise, having low MIL can intensify the potential adverse outcomes of stressors appraised as hindrances. This study aims to investigate how role stressors appraised as either challenges or hindrances may influence anxiety and intention to leave among state police officers in the Brazilian Federal District (DF), as well as implications of MIL as a moderator variable of these relationships. Our hypotheses supported the mediating effect of role stressors’ appraisals in their prediction of police officers’ anxiety and intention to leave their job, and the moderator effects of MIL in these same relationships. Findings are discussed in terms of changes in police regulations and training programs aimed at increasing officers’ MIL and coping strategies to redirect how they appraise role stressors as challenges rather than as hindrances, which may lead to a healthier work experience for DF State Police officers.